A presença da religiosidade no ambiente de trabalho : um estudo de caso - Pupim, Gláucia Tristão (2007)
This dissertation is intended to understand the religion's presence at a selected company's workplace, chose for this specific purpose. To achieve this goal, it was necessary to look for academic constructs related to the issue. The method used for the re